Solve:
(i)
\(\begin{aligned}6-(-7)&=6+7 \\\\&=13. \end{aligned}\)
(ii)
\(\begin{aligned}-21+(3)&=-21+3 \\\\&=-18. \end{aligned}\)
In general,
Calculate:
\(\begin{aligned}9\times(-11)&=-(9\times11) \\\\&=-99. \end{aligned}\)
\(\begin{aligned}-48\div(-8)&=+(48\div8) \\\\&=6 \end{aligned}\)
\(\begin{aligned}&\space49\div(-8+1)\\\\&=49\div(-7) \\\\&=-7. \end{aligned}\)
\(\begin{aligned}&\space\dfrac{22+(-4)}{-7-2} \\\\&= \dfrac{22-4}{-9}\\\\ &=\dfrac{18}{-9}\\ \\&=-2. \end{aligned}\)
Commutative Law
\(\begin{aligned} a+b&=b+a \\\\a\times b&=b\times a \end{aligned}\)
Associative Law
\(\begin{aligned} (a+b)+c&=a+(b+c) \\\\(a\times b)\times c&=a\times(b\times c) \end{aligned}\)
Distributive Law
\(\begin{aligned} a\times(b+c)&=a\times b+a\times c \\\\a\times(b-c)&=a\times b-a\times c \end{aligned}\)
Identity Law
\(\begin{aligned} a+0&=a \\\\a\times 0&=0 \\\\a\times 1&=a \\\\a+(-a)&=0 \\\\a\times\dfrac{1}{a}&=1 \end{aligned}\)
Get your homework done with live tutors’ help